The Use of Code Switching and Code Mixing in the Interpretation of Sundanese into Indonesian in the Learning Process - Eni Karyati; Iis Ristiani (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the forms, functions, and causal factors of code switching and code mixing in the interpretation of Sundanese into Indonesian during the learning process at SDN Sukahurip. This study uses a qualitative descriptive approach with observation, interview, and documentation methods to gain a deep understanding of the linguistic phenomena that occur in learning interactions. The research data sources are teacher and student speech during teaching and learning activities involving the use of two languages, namely Sundanese and Indonesian. Data collection was carried out through observation techniques using observation guidelines assisted by mobile phone recordings, semi-structured interviews with teachers, and documentation studies in the form of field notes and transcription of speech data. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the forms of code switching that emerged include internal and external code switching, while the forms of code mixing include the insertion of words, phrases, and clauses. The main function of using code switching and code mixing in learning is to clarify meaning, create emotional closeness between teachers and students, and adjust the social context in learning interactions. The causal factors include the language habits of teachers and students, the learning situation, and the communicative purpose in the process of delivering the material. Thus, code switching and code mixing can play a role as pedagogical strategies in supporting the effectiveness of communication and understanding of concepts in bilingual learning in elementary schools.